2011
DOI: 10.1111/j.1440-1843.2011.02026.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance characteristics and predictors of yield from transbronchial needle aspiration in the diagnosis of peripheral pulmonary lesions

Abstract: TBNA is the single best contributor to the success of bronchoscopy in the diagnosis of PPLs, and should be routinely used especially in the presence of lesions lacking the bronchus sign. Lesion size of > 2cm, location in the middle lobe, and malignant nature are strong predictors of a positive TBNA result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 26 publications
2
33
0
Order By: Relevance
“…This yield may even be enhanced by additional biopsy techniques, such as needle aspiration with or without endobronchial ultrasound [7][8][9][10][11][12], but were not included in our routine programme in an otherwise operable SPN. Bacterial pneumonia was found to be the cause of the SPN in two cases.…”
Section: Discussionmentioning
confidence: 99%
“…This yield may even be enhanced by additional biopsy techniques, such as needle aspiration with or without endobronchial ultrasound [7][8][9][10][11][12], but were not included in our routine programme in an otherwise operable SPN. Bacterial pneumonia was found to be the cause of the SPN in two cases.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of lobar tumour location on sensitivity or negative predictive values has been sparsely investigated. A bronchoscopic study found the lowest yield when the lesion was in the most apical or basal segment (11), and a TTNAB study found the numerically lowest yield in the right upper lobe (12). The background is not known, but we speculate that the thoracic anatomy of the apical thorax restricts tumour access because of, for example, lower rib–rib distance and larger distance from skin to pleura compared to more distally located lesions.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] The strength of TBNA is that it showed higher sensitivity than transbronchial biopsy, especially in cases with lesions lacking bronchus sign. 15,16) Adding TBNA to conventional EBUS diagnostic procedures has demonstrated a potential for good …”
Section: Discussionmentioning
confidence: 99%